2019
DOI: 10.1101/661165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovering precise temporal patterns in large-scale neural recordings through robust and interpretable time warping

Abstract: 1Though the temporal precision of neural computation has been studied intensively, a data-driven determination 2 of this precision remains a fundamental challenge. Reproducible spike time patterns may be obscured on single 3 trials by uncontrolled temporal variability in behavior and cognition, or may not even be time locked to measurable 4 signatures in either behavior or local field potentials (LFP). To overcome these challenges, we describe a general-5 purpose time warping framework that reveals precise spi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 79 publications
(111 reference statements)
0
44
0
Order By: Relevance
“…Principal components analysis was then applied to this matrix to find the top 3 PCs which were used to visualize the raw activity ( Figure 1B). Next, we used time-warped PCA (https://github.com/ganguli-lab/twpca) 11,33 to find continuous, regularized time-warping functions that align the trials within a single movement condition together. We verified that these warping functions appeared close to the identity line, smoothly bending away from it after the go cue in order to account for variations in writing speed from trial to trial (as can be seen in the example shown in Figure 1B-C).…”
Section: Pen Trajectory Visualizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Principal components analysis was then applied to this matrix to find the top 3 PCs which were used to visualize the raw activity ( Figure 1B). Next, we used time-warped PCA (https://github.com/ganguli-lab/twpca) 11,33 to find continuous, regularized time-warping functions that align the trials within a single movement condition together. We verified that these warping functions appeared close to the identity line, smoothly bending away from it after the go cue in order to account for variations in writing speed from trial to trial (as can be seen in the example shown in Figure 1B-C).…”
Section: Pen Trajectory Visualizationmentioning
confidence: 99%
“…The neural activity appeared to be strong and repeatable, although the timing of its peaks and valleys varied across trials (potentially due to fluctuations in writing speed). We used a timealignment technique to remove temporal variability 11 , revealing remarkably consistent underlying patterns of neural activity that are unique to each character (Fig. 1C).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To directly address the question of correlated jitter within early visual populations, we used a measure inspired by spike count noise correlation: the Spearman correlation (ρ) of jitter across trials (henceforth notated ρjitter). To quantify jitter for each cell, we use a Dynamic Time Warping (DTW) procedure adapted from 61 ( Figure 4A and see Methods). Briefly, a linear time warping procedure is used to fit a temporal shift for each trial that best aligns that trial with all of the other trials via a least-squares loss.…”
Section: Correlated Spike Time Variability (Jitter)mentioning
confidence: 99%
“…Conversely, if one cell tends to "early" when the other is "late", they have a negative ρjitter. The linear DTW method straightforwardly extends to populations to estimate population shifts (ref 61 , Fig 4A right side). We analyzed the correlation of the trial-to-trial shifts estimated from single cells with other single cells (ρjitter) and single cells and variously constructed sub-populations of simultaneously recorded cells (ρglobal jitter).…”
Section: Correlated Spike Time Variability (Jitter)mentioning
confidence: 99%